Hormone Replacement Therapy and Aging: A Potential Therapeutic Approach for Age-Related Oxidative Stress and Cardiac Remodeling. (3rd February 2021) - Szabó, Renáta; Hoffmann, Alexandra; Börzsei, Denise; Kupai, Krisztina; Veszelka, Médea; Berkó, Anikó Magyariné; Pávó, Imre; Gesztelyi, Rudolf; Juhász, Béla; Turcsán, Zsolt; Pósa, Anikó; Varga, Csaba
Abstract : Advanced age is an independent risk factor for cardiovascular diseases, which might be further exacerbated by estrogen deficiency. Hormone replacement therapy (HRT) decreases cardiovascular risks and events in postmenopausal women; however, its effects are not fully elucidated in older individuals. Thus, the aim of our study is to examine the impact of HRT on oxidant/antioxidant homeostasis and cardiac remodeling. In our experiment, control (fertile) and aging ( 20-month-old) female Wistar rats were used. Aging rats were further divided into estrogen- (E2, 0.1 mg/kg/day per os ) or raloxifene- (RAL, 1.0 mg/kg/day per os ) treated subgroups. After 2 weeks of treatment, cardiac heme oxygenase (HO) activity, total glutathione (GSH) content, matrix metalloproteinase-2 (MMP-2) activity, and the concentrations of collagen type I and tissue inhibitor of metalloproteinase (TIMP-2), as well as the infarct size, were determined. The aging process significantly decreased the antioxidant HO activity and GSH content, altered the MMP-2/TIMP-2 signaling, and resulted in an excessive collagen accumulation, which culminated in cardiovascular injury. However, 2 weeks of either E2 or RAL treatment enhanced the antioxidant defense mechanisms and attenuated cardiac remodeling related to aging. Our findings clearly show that 2-week-long HRT is a potential intervention to bias successful cardiovascular aging via reducing oxidative damage and cardiovascular dysfunction.